The language of dying: Communication about end-of-life in residential aged care. Issue 3 (16th March 2022) - Omori, Maho; Jayasuriya, Jude; Scherer, Sam; Dow, Briony; Vaughan, Marie; Savvas, Steven
Abstract: This article explores implications of language used in communicating death and dying in residential aged care, which increasingly emphasizes a "family-centered" approach to end-of-life care. Based on focus groups with care professionals and families, our findings reveal a persistent clinical culture that resists frank discussions of dying, with many staff preferring to use euphemisms for dying. Our results emphasize the importance of end-of-life education for families, which families acknowledged was lacking. Cultural change in institutional control over disclosing dying is imperative in order to gain family trust and support in professional care and promote death literacy.